A relational perspective on deliberative systems: combining interpretive and structural analysis. Issue 1 (2nd January 2020) - Holdo, Markus
ABSTRACT: Deliberative systems theory suggests that a democratic society works well when citizens' experiences and views, as expressed in various forms and sites of communication, are connected and taken up by other citizens as well as policy-makers. Pluralism, which is not always easily reconciled with high-quality deliberation in every instance, is seen as instrumental to the realization of democratic values and sound decision-making. This perspective raises new methodological challenges, such as (1) identifying sites of communication that serve important functions in a deliberative system, (2) connecting different sites and (3) assessing their impact. Recent scholarship has found that these challenges can be fruitfully met by applying interpretive methodology, which, like deliberative systems theory, aims to understand social interactions on their own terms, and not by measuring their correspondence to theoretical ideal-types. However, for theory development, as well as to help improve actual deliberative systems, researchers also need to make generalizable inferences. This paper develops a relational approach that combines interpretive methods with structural theory, which allows researchers to assess and explain the deficiencies, as well as the opportunities, that citizens experience. The principles of relational analysis are illustrated by research on citizen deliberation about urban riots.